ANALISIS KONTROVERSI CROWDFUNDING PEMBANGUNAN MASJID OLEH DAUD KIM PADA AKUN YOUTUBE @KOREAREOMIT - Hartono, Toni; Arianti; Sinaga, Ruwaida; Daruqutni, Imam; Husyaini, Arwin (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Technological advancements have driven the emergence of crowdfunding as a digital platform for fundraising. This study analyzes the controversy surrounding the fundraising initiative for the construction of a mosque in Daegu, South Korea, led by YouTuber Daud Kim through crowdfunding, and examines the concept from an Islamic perspective. The research employs a qualitative method with a netnographic approach, collecting data from social media, particularly the YouTube account @KoreaReomit. The findings indicate that the controversy arose due to the use of Daud Kim’s personal PayPal account, a lack of transparency, and non-compliance with the regulations set by the Muslim student community in Daegu. Kemajuan teknologi mendorong munculnya sistem crowdfunding sebagai sarana penggalangan dana digital. Penelitian ini menganalisis kontroversi penggalangan dana pembangunan masjid di Daegu, Korea Selatan, oleh YouTuber Daud Kim melalui crowdfunding, serta meninjau konsepnya dalam perspektif Islam. Metode yang digunakan adalah kualitatif dengan pendekatan netnografi melalui media sosial, khususnya akun YouTube @Korea Reomit. Hasil penelitian menunjukkan bahwa kontroversi muncul akibat penggunaan akun PayPal pribadi, kurangnya transparansi, serta ketidaksesuaian dengan aturan komunitas mahasiswa Muslim di Daegu.